Pengembangan Digital Marketing Pantai Ujung dan Bakti Sosial Yayasan Al-Kahfi Kampung Tua Teluk Mata Ikan - Anggra Priyansah; Bagus Prasetya Faozanzen; Grace Tama Rosalinda; Etty Sri Wahyuni; Diana Titik Windayati; Asnira Asnira; Muhammad Ridho; Mega Kurnia; Casandra Casandra (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
This Real Work Lecture (KKN) activity was carried out in Kampung Tua Teluk Mata Ikan, Batam, with the aim of making a real contribution to the community through two main programs, namely the development of digital marketing for Ujung Beach tourist destinations and the implementation of social service activities at the Al-Kahfi Foundation. The problems faced by partners are the lack of digital promotion strategies for tourism potential and the limited support of adequate social facilities at the foundation. To overcome these problems, this service activity uses field observation methods, digital marketing training, mutual cooperation on environmental cleanliness, and socialization to the community and foundation administrators. The training includes social media content creation, digital account management, and internet-based marketing strategies to increase the attractiveness of Ujung Beach as a local tourist destination. In addition, social activities are carried out through joint community service, provision of basic needs assistance, and clean environment education. The results of the implementation of this program show an increase in public awareness of the importance of using digital technology for tourism promotion, as well as the creation of a cleaner, neater, and more comfortable social environment. The enthusiasm of the community and the foundation showed a positive response to this activity, which contributed to strengthening the socio-economic capacity of the residents. Overall, this KKN program not only provides a short-term impact in the form of improving skills and environmental cleanliness, but also encourages the sustainability of local tourism development and community empowerment. The active involvement of students in the planning and evaluation process also strengthens the spirit of collaboration and social concern which is the main basis of this service activity.